2015
DOI: 10.1111/hiv.12321
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in the health care system contribute to a high rate of late HIV diagnosis in Sweden

Abstract: Deficiencies in the health care system with missed HIV testing opportunities contribute to the high proportion of late presenters in Sweden, especially among migrants. With increased testing at immigration and further incorporation of "indicator-guided" testing in general practice, most patients could be diagnosed earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 28 publications
2
71
0
1
Order By: Relevance
“…25 A majority (57%) of WLWH in our study had at one point been highly immunosuppressed (median nadir CD4 count 178 cells/lL), which in the majority of cases is due to late HIV diagnosis. 26 As shown earlier, 7,21,22 the risk of highgrade cervical intraepithelial neoplasia increased with immunosuppression among our patients. This indicates the importance of an early HIV diagnosis since an early start of ART will prevent the development of immunosuppression.…”
Section: Discussionsupporting
confidence: 76%
“…25 A majority (57%) of WLWH in our study had at one point been highly immunosuppressed (median nadir CD4 count 178 cells/lL), which in the majority of cases is due to late HIV diagnosis. 26 As shown earlier, 7,21,22 the risk of highgrade cervical intraepithelial neoplasia increased with immunosuppression among our patients. This indicates the importance of an early HIV diagnosis since an early start of ART will prevent the development of immunosuppression.…”
Section: Discussionsupporting
confidence: 76%
“…The vast majority of LP in Sweden are migrants [6], but in the present study we showed that symptomatic patients from high prevalent countries were less likely to be missed by the physician at seeking health care and also to neglect their symptoms, compared to patients born in Sweden. The finding of a higher testing rate of migrants shows a good adherence to the epidemiological indicators for testing among health care professionals [17].…”
Section: Discussionmentioning
confidence: 48%
“…This cohort represented three quarters of all newly diagnosed patients from all parts of the country with an equal geographical distribution including the major cities and county clinics and has previously been described in detail [6]. All participants provided their written informed consent and the study was approved by the Regional Ethical Review Board in Stockholm, Sweden (2009/1029-31/1-4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations